PENETAPAN PERKIRAAN KADAR LOW DENSITY LIPOPROTEIN (LDL), HIGH DENSITY LIPOPROTEIN (HDL) DAN RASIO LDL TERHADAP HDL PADA POPULASI DATA RISKESDAS TAHUN 2007 - , Iskandar; , dr. Budi Yuli Setianto, SpPD, K-KV, SpJP (K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Coronary Heart Disease (CHD) occurs due to narrowing of coronary arteries. The risk factor of CHD is dyslipidemia, These is abnormality of lipid metabolism showed by increased LDL or HDL cholesterol decreased in the plasma. The ratio of LDL to HDL is also an indicator to describe the risk of CHD. The risk increased progressively by increasing levels of serum LDL and will be protective in the high concentrate of HDL. The risk factors are age, sex, food habit, smoking, lack of activity, and obesity. Objective: To determine the approximate levels of LDL, HDL, and the ratio LDL to HDL, and factors related to levels of LDL, HDL, and the ratio LDL to HDL. Method: This was an analytical research with Cross-sectional design by reviewing analysis of secondary data of Riskesdas 2007 data. The population is all subjects which were tested of blood specimens. This was a total sampling and the total number of sample was 7.740 people. Statistical analysis were T-test, Anova and Regression to determine the most affected risk factor. Results: The mean of LDL, HDL, and the ratio LDL to HDL, in the population (125,59 ± 35,78 mg/dl, 43,32 ± 12,79 mg/dl, and 3,15 ± 1,41 mg/dl), in heart disease patients (125,45 ± 35,71 mg/dl, 43,29 ± 12,72 mg/dl, and 3,15 ± 1,41 mg/dl), in patients with heart disease ( 136,20 ± 38,62 mg/dl, 45.67 ± 17,37 mg/dl, and 3,29 ± 1,41 mg/dl). There were sex effect (p